Disease-Associated PNPLA6 Mutations Maintain Partial Functions When Analyzed in Drosophila - Sunderhaus, Elizabeth R.; Law, Alexander D.; Kretzschmar, Doris (Frontiers in Neuroscience, 2019)
Mutations in patatin-like phospholipase domain-containing protein 6 (PNPLA6) have been linked with a number of inherited diseases with clinical symptoms that include spastic paraplegia, ataxia, and chorioretinal dystrophy. PNPLA6 is an evolutionary conserved protein whose orthologue in Drosophila is Swiss-Cheese (SWS). Both proteins are phospholipases hydrolyzing lysophosphatidylcholine (LPC) and phosphatidylcholine (PC). Consequently, loss of SWS/PNPLA6 in flies and mice increases both lipids and leads to locomotion deficits and neurodegeneration. PNPLA6 knock-out mice are embryonic lethal, and a mutation creating an early stop codon in human PNPLA6 has only been identified in compound heterozygote patients. In contrast, disease-causing point mutations are found in homozygous patients, with some localized in the phospholipase domain while others are in a region that contains several cNMP binding sites. To investigate how different mutations affect the function of PNPLA6 in an in vivo model, we expressed them in the Drosophila sws1 null mutant. Expressing wild type PNPLA6 suppressed the locomotion and degenerative phenotypes in sws1 and restored lipid levels, confirming that the human protein can replace fly SWS. In contrast, none of the mutant proteins restored lipid levels, although they suppressed the behavioral and degenerative phenotypes, at least in early stages. These results show that these mutant forms of PNPLA6 retain some biological function, indicating that disruption of lipid homeostasis is only part of the pathogenic mechanism. Furthermore, our finding that mutations in the cNMP binding sites prevented the restoration of normal lipid levels supports previous evidence that cNMP regulates the phospholipase activity of PNPLA6.